Challenge of hepatitis B testing following intravenous immunoglobulin therapy in patients with autoimmune skin diseases. Issue 10 (21st June 2022) - Pruessmann, Jasper N.; Langan, Ewan A.; Rupp, Jan; Marquardt, Jens; Terheyden, Patrick; Zillikens, Detlef; Ludwig, Ralf J.; Boch, Katharina
Abstract: Intravenous immunoglobulin (IVIg) contains pooled immunoglobulins from the plasma of healthy blood donors. All plasma samples are tested for HIV, hepatitis viruses (A, B, and C), and parvovirus B19. As part of this screening step, nucleic acid amplification technology (NAT) is used and allows the presence of specific antibodies targeting viral structures that are commonly used to test for infection status, such as anti‐hepatitis B surface antigen (HBs) or anti‐hepatitis B virus core (HBc) antibodies. For this reason, manufacturers point to the possibility of false‐positive viral serological test results following IVIg treatment due to the passive transfer of antibodies. IVIg therapy is commonly used to manage patients with severe, treatment‐refractory autoimmune skin diseases. The aim of this cohort study was to retrospectively quantify newly‐discovered positive serological HBV test results after IVIg treatment in patients with autoimmune skin diseases. Between March 2018 and June 2021, 28 patients with autoimmune skin diseases received IVIg therapy, of whom 17 were longitudinally followed‐up. None of the patients had evidence of active HBV infection prior to IVIg therapy. All patients (n = 17) had detectable anti‐HBs antibodies and 12 patients had anti‐HBc antibodies 4 weeks after commencing IVIg treatment. Passive antibody transfer seems the most likely interpretation. Nevertheless, complete serological hepatitis assessment should be performed to exclude a new infection. We recommend hepatitis screening before IVIg therapy to prevent diagnostic confusion which may arise due to passive antibody transfer.